2022
DOI: 10.3389/fimmu.2022.809761
|View full text |Cite
|
Sign up to set email alerts
|

A New Trend in Cancer Treatment: The Combination of Epigenetics and Immunotherapy

Abstract: In recent years, immunotherapy has become a hot spot in the treatment of tumors. As an emerging treatment, it solves many problems in traditional cancer treatment and has now become the main method for cancer treatment. Although immunotherapy is promising, most patients do not respond to treatment or develop resistance. Therefore, in order to achieve a better therapeutic effect, combination therapy has emerged. The combination of immune checkpoint inhibition and epigenetic therapy is one such strategy. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 135 publications
0
34
0
Order By: Relevance
“…A large number of preclinical studies have revealed the critical role of epigenetic factors in antitumor immune responses and reversal of immunosuppression, particularly in PD-L1/PD-1 blockade (72,91,172,184). The rational application of a combination of multiple epigenetic targeted drugs, including DNMT inhibitors and histone-modifying enzyme inhibitors, with anti-PD-L1 immunotherapy, represents an opportunity to improve antitumor efficacy, enhance response rates to PD-1/PD-L1 blocking antibodies and reverse drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of preclinical studies have revealed the critical role of epigenetic factors in antitumor immune responses and reversal of immunosuppression, particularly in PD-L1/PD-1 blockade (72,91,172,184). The rational application of a combination of multiple epigenetic targeted drugs, including DNMT inhibitors and histone-modifying enzyme inhibitors, with anti-PD-L1 immunotherapy, represents an opportunity to improve antitumor efficacy, enhance response rates to PD-1/PD-L1 blocking antibodies and reverse drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chemotherapy, one of the most widely used therapeutic methods is radiotherapy [ 4 ], which can be used to measure the size of each tumor. Recently, immunotherapy has also become a popular tumor treatment method [ 5 ]. Immunotherapy for cancer involves using and controlling the immune system of cancer patients to kill cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent challenges include discovering why immunotherapy works so dramatically in some patients but not in others, and how to design a multipronged approach for a complete curative regimen in a patient-specific manner. Accumulating evidence has highlighted the importance of epigenetic mechanisms in determining T-cell fates and the corresponding features of immunotherapy-responsive T cells, while epigenetic drugs have been demonstrated to improve cancer immunotherapy efficacy in many aspects ( Liu et al, 2022 ). In this Research Topic “ Combinatory approaches of epigenetic regulators in T cell-based immunotherapy ”, a diverse range of examples are included that cover methodological approaches of multi-omics analysis and biomarker exploration, together with clinical studies and literature reviews of research progress made in current epigenetic and immunotherapy combinatory approaches.…”
mentioning
confidence: 99%